Negative cutaneous effects of medicinal plants in Senegal. (24th July 2015) - Niang, S.O.; Tine, Y.; Diatta, B.A.; Diallo, M.; Fall, M.; Seck, N.B.; Kane, A.
Summary: Use of medicinal plants is common and widespread throughout Africa, including in Senegal. Because efficacy has been demonstrated, public policies have been instituted that have allowed plant‐based therapies to have an important role in general primary care. However, little is known about the cutaneous safety of many plant‐based therapies. In this 6‐month prospective study all cases of dermatitis induced or aggravated by exclusive use of medicinal plants were evaluated via skin allergy testing. The results were classified and compared with the available literature. Forty‐three cases of plant‐therapy‐associated cutaneous reactions were identified, including worsening of existing conditions (56%), recurrence of a previously resolved condition (16%) and new dermatitis arising spontaneously (28%). In the cases where the condition was new, generalized exfoliative dermatitis occurred in 42% of cases with an average time of onset of 9 days. Specific plants were identified in 65% of cases and included 18 varieties. The frequency and severity of plant‐induced cutaneous reactions should be the basis for the creation of a phytovigilance programme and re‐evaluation of how traditional medicine is used in the general population. When irritation occurs, identification of the responsible plant and allergy testing should be the first steps towards relieving symptoms.